Ocenka nekotorych pokazatelej biochimiceskogo statusa bokserov - Radzhabkadiev, R. M.; Kobelkova, I. V.; Vybornaya, K. V.; Lavrinenko, S. V.; Semyonov, M. M.; Sokolov, A. I.; Nikityuk, D. B. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
34 professional junior boxers of different weight categories were examined. The average age of the subjects was 20.3 ± 1.4 years. We studied some biochemical parameters in the blood serum of athletes (activity of alaninamino- and aspartate aminotransferase (ALT, AST), creatine phosphokinase (CPK), alkaline phosphatase (ALP), blood levels of lactic acid, cortisol, testosterone, b-CrossLaps, Fe and Ca. Found a significant (2.2 times) excess of the activity of CPK in 50% of the examined athletes. The coefficient of variation of the activity of this enzyme was equal to 90%. In 85% of cases the ratio CPK/AST activity higher than the physiological norm, indicating the presence of the examined damageto muscle cells. All athletes observed a high content of lactate in the blood serum on average 73% higher than the physiological norm. In 78% of the surveyed revealed a moderate excess of cortisol in the blood. The testosterone content of all athletes was within the physiological norm. The anabolism index did not exceed 2%, indicating a pronounced overtraining of the subjects. The serum concentration of Cross-Laps-B in all examined athletes significantly exceeded normal values and averaged 1.3 ± 0.38 ng/ml. The data obtained probably indicate a high degree of bone tissue microtraumatics in boxers.